Analysis of the Urgency of the Application of Social and Cultural Elements in the Early Childhood Education Sector - Ni Putu Listiawati; Demsy Jura; Margaret Stevani; Mohammad Abdul Mukhyi (HK-Publishing, 2022)
AbstractEducation is very important, and very helpful in the growth and development of the human brain. That's why education should be given to humans from an early age. Because at that age, humans are still very easy to learn something. The social and cultural system becomes a form of the totality of values in society. Good social order values, behavior, and so on. The social and cultural system is also an embodiment of the community itself, so it is very important for the community in it to know, study and also instill the social and cultural values of the community where they live. However, because culture has several unwritten forms and is so numerous, it will be very difficult to remember and practice all of them for people who are adults and already have a certain mind-bearing burden. An effective way for this culture to be attached to a person's personality is to introduce and teach it to individuals from an early age. Culture needs to be taught to children at an early age so that they do not get along and have bad habits in social relationships. However, it is unfortunate that education with social and cultural elements is not significant and still has a small portion. There are still many PAUD, Kindergarten, Play Group, and other early childhood education institutions that have not implemented it optimally. They mostly focus on how to raise children and teach them to read, write and count. Meanwhile, after the children enter Elementary School (SD), it becomes less and less difficult for them to learn materials with social and cultural elements.Keywords: Social, Culture, Early Childhood Education AbstrakPendidikan sangat penting, dan sangat membantu dalam pertumbuhan dan perkembangan otak manusia. Karena itulah pendidikan harus diberikan kepada manusia sejak dini. Karena pada usia tersebut, manusia masih sangat mudah mempelajari sesuatu. Sistem sosial budaya menjadi bentuk totalitas nilai dalam masyarakat. Tatanan sosial yang baik nilai, perilaku, dan sebagainya. Sistem sosial budaya juga merupakan perwujudan dari masyarakat itu sendiri, sehingga sangat penting bagi masyarakat di dalamnya untuk mengetahui, mempelajari dan juga menanamkan nilai-nilai sosial budaya masyarakat tempat mereka tinggal. Namun, karena budaya memiliki beberapa bentuk yang tidak tertulis dan jumlahnya sangat banyak, maka akan sangat sulit untuk mengingat dan mempraktikkan semuanya bagi orang yang sudah dewasa dan sudah memiliki beban pikiran tertentu. Cara efektif agar budaya ini melekat pada kepribadian seseorang adalah dengan mengenalkan dan mengajarkannya kepada individu sejak dini. Budaya perlu diajarkan kepada anak sejak dini agar tidak bergaul dan memiliki kebiasaan buruk dalam pergaulan. Namun sangat disayangkan pendidikan dengan unsur sosial budaya tidak signifikan dan masih memiliki porsi yang kecil. Masih banyak PAUD, TK, Play Group, dan lembaga pendidikan anak usia dini lainnya yang belum melaksanakannya secara optimal. Mereka kebanyakan fokus pada bagaimana membesarkan anak-anak dan mengajari mereka membaca, menulis, dan berhitung. Sementara itu, setelah anak-anak memasuki Sekolah Dasar (SD), mereka semakin sulit untuk mempelajari materi-materi yang mengandung unsur sosial budaya.Kata kunci: Sosial, Budaya, Pendidikan Anak Usia Dini